Prevalence of possible depression and associated biosocial risk factors among adolescents in a private school in Chennai, South India - Kumaravel Kanagavelu, Aravind Sunderavel; Chidambaram, Vishnu; Jayachandar, Subalakshmi (International Journal of Contemporary Pediatrics, 2019)
Background: Depression among adolescents is often undetected because of lack of awareness in mental health. Schools are the best place to study, analyze and report adolescent depression. The objective of this survey is to find out the prevalence of possible depression and associated bio-social risk factors among high school going adolescents aged 15 and 16 years. This can help reform school curriculum based on the prevalence of depression. Methods: A school based cross-sectional study done by randomly selecting 10 classrooms from the 11th standard high school compartment in a private school. Data was collected using a pre-designed and structured questionnaire based on Kutcher’s Adolescent Depression Scale. The results were analyzed using R Studio software with Pearson Chi-square test and a p-value of <0.05 was considered statistically significant. Results: Out of 486 students included in the study, 164(33.7%) have ‘possible depression’ and adolescents aged 16 years(39.5%) has higher proportion of possible depression than adolescents aged 15 years(29.2%), which is statistically significant(p=0.016). About 46.2% of adolescents having illiterate mothers had a possibility of depression. With regards to physical activity 28.1% who played for 3 hours and more had depressive signs and adolescents who played less had 37.2%. This difference is statistically significant (p=0.039). Conclusions: Being a dormant and hidden disease, depression is one such disease that must be probed by regular health screening. Mother’s literacy status and a modifiable factor ‘physical activity’ have shown promising statistical significance. Adequate physical activity must be included in school curriculum to reduce the risk of depression.